Odontological education in 7-9 year old scholars of Andrés Rázuri School of San Martín de Porres district - Evaristo Chiyong, Teresa (2007)
An educational program on oral health prevention with a strong component based on playful strategy was developed for 28 children, 7 - 9 year olds from the Andrés Razuri school of San Martin de Porres district. The level of knowledge of the children was evaluated before and after the intervention showing that before no one recognized dental caries as a disease, after receiving the pertinent information, 37 % of them did, and 67 % can recognize 4 factors that generate them. They recognize 3 basic hygienic basic elements which changed from 46.4 % to 88 %, the concept of the moments of tooth brushing was changed so that they associated them with the ingestion of food of 17.9 % to 56 %, the identification of seals as a preventive element varied from 28 % to 74 %, then we conclude that the levels of knowledge were inverted by the efficiency of the proposed strategies, reaffirming that the education based on the game provides positive results in the infantile population.